2021
DOI: 10.1016/j.apsb.2020.10.012
|View full text |Cite
|
Sign up to set email alerts
|

The phytochemical, biological, and medicinal attributes of phytoecdysteroids: An updated review

Abstract: The phytoecdysteroids (PEs) comprise a large group of biologically-active plant steroids, which have structures similar to those of insect-molting hormones. PEs are distributed in plants as secondary metabolites that offer protection against phytophagus (plant-eating) insects. When insects consume the plants containing these chemicals, they promptly molt and undergo metabolic destruction; the insects eventually die. Chemically, ecdysteroids are a group of polyhydroxylated ketosteroids that are structurally sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 171 publications
0
58
0
1
Order By: Relevance
“…Phytoecdysteroids (PE) are a wide group of plant steroids whose structure is characterized by a steroid skeleton 5β-cholestanol containing a 6-ketone ring B and a hydroxyl group in position C-14α [63]. They occur as polar and non-polar conjugates, including esters of aliphatic and phenolic acids, sulfate and phosphate, ethers, and glycosides.…”
Section: Phytoecdysteroidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phytoecdysteroids (PE) are a wide group of plant steroids whose structure is characterized by a steroid skeleton 5β-cholestanol containing a 6-ketone ring B and a hydroxyl group in position C-14α [63]. They occur as polar and non-polar conjugates, including esters of aliphatic and phenolic acids, sulfate and phosphate, ethers, and glycosides.…”
Section: Phytoecdysteroidsmentioning
confidence: 99%
“…They occur as polar and non-polar conjugates, including esters of aliphatic and phenolic acids, sulfate and phosphate, ethers, and glycosides. Despite being widespread, a small percentage of plants contain detectable levels of PE [63]. The compound 20-Hydroxyecdysone (20 HE) is the most common phytoecdysteroid.…”
Section: Phytoecdysteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the absolute stereochemistry of compounds 1 and 2 , which can be crucial for the biological activity, was not determined, it is assumed that they are 2 S ,3 R ,14 S ,20 R ,22 R ,25-hexahydroxy-5 S -cholest-7-en-6-one (2β,3β,14α,20 R ,22 R ,25-hexahydroxy-5β-cholest-7-en-6-one) and 2 S ,3 R ,5 S, 14 S ,20 R ,22 R ,25-heptahydroxy-5 S -cholest-7-en-6-one (2β,3β,5β,14α,20 R ,22 R ,25-heptahydroxy-5β-cholest-7-en-6-one), respectively, as established by X-ray crystallographic studies [ 28 ], which confirmed an earlier established structure of an ecdysone skeleton [ 29 ]. Additionally, one general route of ecdysone biosynthesis in plants has been established without variability in the stereochemistry, except for the trans or cis junction of A/B rings [ 10 , 30 ]. Moreover, any epimeric form would be recognized by an apparent change in the multiplicity and magnitude of coupling constants of a methine 1 H NMR signal at a chiral center, and a chemical 13 C NMR shift of the vicinal carbon signal, as exemplified by 22 R and 22 S epimers of 20-hydroxyecdysone [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both are dominant ecdysteroids in L. flos-cuculi [ 6 ]. The adaptogenic, anabolic, and neuroprotective properties of ecdysteroids have been widely reported and reviewed [ 8 , 9 , 10 ]. Their multidirectional activity also includes an antimicrobial effect, which, according to some studies, is especially attributed to less polar derivatives [ 11 ].…”
Section: Introductionmentioning
confidence: 99%